Vaccinia topoisomerase and Cre recombinase catalyze direct ligation of activated DNA substrates containing a 3′-para-nitrophenyl phosphate ester - Woodfield, George (Oxford University Press, 2000)
DNA topoisomerases and DNA site-specific recombinases are involved in a diverse set of cellular processes but both function by making transient breaks in DNA. Type IB topoisomerases and tyrosine recombinases cleave DNA by transesterification of an active site tyrosine to generate a DNA–3′-phosphotyrosyl–enzyme adduct and a free 5′-hydroxyl (5′-OH). Strand ligation results when the 5′-OH attacks the covalent complex and displaces the enzyme. We describe the synthesis of 3′-phospho-(para-nitrophenyl) oligonucleotides (3′-pNP DNAs), which mimic the natural 3′-phosphotyrosyl intermediate, and demonstrate that such pre-activated strands are substrates for DNA ligation by vaccinia topoisomerase and Cre recombinase. Ligation occurs by direct attack of a 5′-OH strand on the 3′-pNP DNA (i.e., without a covalent protein–DNA intermediate) and generates free para-nitrophenol as a product. The chromogenic DNA substrate allows ligation to be studied in real-time and in the absence of competing cleavage reactions and can be exploited for high-throughput screening of topoisomerase/recombinase inhibitors.